An international approach to estimating the indications and number of eligible patients for carbon ion radiation therapy (CIRT) in Australia - Ahern, Verity; Adeberg, Sebastian; Fossati, Piero; Garrett, Richard; Hoppe, Bradford; Mahajan, Anita; Orlandi, Ester; Orecchia, Roberto; Prokopovich, Dale; Seuntjens, Jan; Thwaites, David; Trifiletti, Daniel; et al. (Radiotherapy and oncology, 2023)
To establish the treatment indications and potential patient numbers for carbon ion radiation therapy (CIRT) at the proposed national carbon ion (and proton) therapy facility in the Westmead precinct, New South Wales (NSW), Australia.
Gesehen am 29.11.2023